Validity and reliability of the Malaysian version of parent attitudes about Childhood Vaccines (PACV) survey - Awadh, Ammar Ihsan Jawad; Ab. Hadi, Hazrina; Khairuddin, Mawaddah (Elsevier Inc., 2016)
The number parents in Malaysia that are hesitant about vaccines has grown in recent years. Identifying these parents is important in order to implement the necessary measures to maintain and improve the vaccines intake. The objectives of this study were to translate the Parent Attitudes about Childhood Vaccines (PACV) survey into Bahasa Malaysia, and to assess the reliability and construct a validity of the translated survey.